Τα ιδανικά και οι στόχοι ζωής των ηρώων και των ηρωίδων στα θεατρικά έργα για παιδιά - Κλαδάκη Μαρία (Παιδαγωγικά ρεύματα στο Αιγαίο, 2022)
This paper examines the ideals and life goals of male and female heroes (adults and underage) as reflected in theatrical plays for children. The method used in the research was based on content analysis (quantitative-qualitative). As classification unit we defined the person (the character), while as context unit we used the meaning module. Research material analysis indicated that the heroes of theatrical plays for children have both high goals and ideals. Thanks to their combative and forceful character, they successfully face social phenomena, resist against authoritarian regimes, battle against social injustice, etc. On the contrary, female heroes do not seem to be fighting for some higher goal or they don’t appear in the research texts as struggling for any ideals. Similarly, in underage characters, boys are the ones setting high goals: saving the planet, humanity, struggling for peace in the world and endeavouring for a cleaner environment for everyone. Girls, on the other hand, not only appear as not having high goals in their lives but more often than not they seem not to realise current everyday life problems altogether.